A worksite-based self management program to improve men's health in rural Western Australia: The industry "waist" disposal project - Holloway, Kristi Maree (Curtin University, 2015)
Men in rural areas are at an increased risk of obesity and chronic diseases. A mixed method study tested the feasibility and impact of a multiphase self-management program at reducing risk factors for chronic disease for 87 men across six worksites in regional Western Australia. The intervention was effective at targeting key health outcomes. Applied strategies were acceptable and are transferable to other male groups in rural areas, where access to interventions is often limited.